Soft Matrix Combined With BMPR Inhibition Regulates Neurogenic Differentiation of Human Umbilical Cord Mesenchymal Stem Cells - Sun, Yingying; Xu, Ziran; Wang, Meijing; Lv, Shuang; Wu, Haitao; Chi, Guangfan; Li, Lisha; Li, Yulin (Frontiers in Bioengineering and Biotechnology, 2020)
Stem cells constantly encounter as well as respond to a variety of signals in their microenvironment. Although the role of biochemical factors has always been emphasized, the significance of biophysical signals has not been studied until recently. Additionally, biophysical elements, like extracellular matrix (ECM) stiffness, can regulate functions of stem cells. In this study, we demonstrated that soft matrix with 1–10 kPa can induce neural differentiation of human umbilical cord mesenchymal stem cells (hUC-MSCs). Importantly, we used a combination of soft matrix and bone morphogenetic protein receptor (BMPR) inhibition to promote neurogenic differentiation of hUC-MSCs. Furthermore, BMPR/SMADs occurs in crosstalk with the integrinβ1 downstream signaling pathway. In addition, BMPR inhibition plays a positive role in maintaining the undifferentiated state of hUC-MSCs on the hydrogel substrate. The results provide further evidence for the molecular mechanisms via which stem cells convert mechanical inputs into fateful decisions.